Pedagogical Leadership to Restructure Teaching Beliefs and Improve Classroom Practices in Mapuche Context - Mellado-Hernández, María Elena (2016)
This article aims to describe the pedagogical beliefs about teaching, learning and assessment underlying the practices of teaching in a rural Mapuche school, located in La Araucania, Chile. The study is executed in an educational research approach, uses a mixed descriptive character methodology. Participants are professionals in managerial and teaching positions in a school that includes transitional level up to 6th grade in the subjects of language/communication and history, geography and social sciences. To collect information on the beliefs, a questionnaire of Likert type scale was used; also, class observations were carried out through ethnographic records to all teachers of the center. Based on the results, it was possible to identify contradictions in the reference frames in both populations because they express both traditional and contemporary pedagogical beliefs. Meanwhile, in the classroom only traditional teaching practices that ignore the Mapuche context are observed. They show rote learning activities and use, preferably, summative evaluation. As a result, it can be concluded that teachers have ambiguities of conceptions in their pedagogical beliefs, it prevails a traditional approach in their classroom practices. Therefore, it is recommended to develop an effective educational leadership that systematically fosters collaborative thinking among peers as a strategy to enable the reconstruction of educational beliefs of principals and teachers.